Visuospatial versus visuomotor activity in the premotor and prefrontal cortex of a primate - di Pellegrino, G (J Neurosci, 1993)
When visuospatial stimuli instruct a limb movement, the stimulus can be said to have both sensory and sensorimotor aspects. We studied the premotor and prefrontal areas of a rhesus monkey in order to identify neuronal activity related to the motor (or instructional) aspects of such stimuli. A rhesus monkey chose limb-movement targets according to one of two rules: (1) visuospatial stimuli instructed and triggered a limb movement toward their locations or (2) identical stimuli triggered a movement toward a predetermined target regardless of their location. Gaze and head fixation assured that each stimulus appeared at a constant location in both retinocentric and craniocentric coordinates, as well as in allocentric space. The task required that the spatial location cued by certain stimuli had to be either remembered or attended after stimulus presentation and before movement. Thus, the visuospatial information presented under one rule differed from that presented under the other only in its motor (instructional) significance and not in its attentional, spatial, mnemonic, or strictly sensory aspects. We could thereby test and confirm the hypothesis that the motor significance of visuospatial cues should commonly affect neuronal activity in the premotor cortex, but less commonly do so in the prefrontal cortex.